Colourism, racism and identity. Didactic strategies to promote their discussion in the classroom (Ogigia. Revista Electrónica de Estudios Hispánicos, 2021)
This paper aims to examine the perceptions that university students have of several sensitive topics in the English-speaking Caribbean such as skin bleaching, xenophobia or rivalry among different ethnic communities of this context. Through innovative resources and the Spanish language as the medium for communication, we examine their impressions from a qualitative point of view in order to conceive coherent intervention programmes and an inclusive curriculum that better reflects their reality. Bearing this goal in mind, we suggest a typology of intercultural activities that proved to be effective. The overall results showed a change of perspective in students, an evident increase of the intercultural communicative competence as well as the ethical and moral benefits resulting from facing these realities in the classroom.
Keywords: colourism; racism; Spanish as a foreign language; higher education; English speaking Caribbean